Scrapbook Fundamentals : Your Guide to Getting Started - Published by Memory Markers Books (Denver, Colorado Memory Makers Books, 2006)
An illustrated guide to organizing photos and memorabilia for scrapbooking; along with advice on journaling, basic design principles, tools, and supplies.
Include Color Illustration, Glossary and Index
Keywords: Photograph albums -- Photographs--Conservation and restoration -- Scrapbooking